Meta-analysis and functional effects of the SLC30A8 rs13266634 polymorphism on isolated human pancreatic islets. - Cauchi, S; Del Guerra, S; Choquet, H; D'Aleo, V; Groves, C; Lupi, R; McCarthy, M; Froguel, P; Marchetti, P (2010)
BACKGROUND: The C-allele of rs13266634 located in SLC30A8 (ZNT8) has been strongly associated with decreased insulin release and with type 2 diabetes (T2D) susceptibility in some but not all studies. To shed further light on this issue, we performed a meta-analysis of the association between rs13266634 and T2D in different ethnic groups and assessed the relationships between SLC30A8 genotypes and some properties of isolated human islets. METHODS: From 32 original articles, a total of 77,234 control individuals and 44,945 subjects with T2D were studied in meta-analysis. To assess the relationships between SLC30A8 genotype and islet cell phenotype, insulin secretion in response to glucose, glucose plus arginine and glucose plus glibenclamide was determined in pancreatic islets isolated from 82 multiorgan donors genotyped for the rs13266634 polymorphism. Quantitative expression of SLC30A8, Insulin and Glucagon mRNA was also measured. RESULTS: Overall, each SLC30A8 risk allele was associated with a 14% increased risk for T2D (P=2.78 x 10(-34)). The population risk of T2D attributable to this polymorphism was estimated at 9.5% in Europeans and 8.1% in East Asians. Basal and stimulated insulin secretion from human islets as well as islet expressions of SLC30A8, Insulin and Glucagon were not affected by the presence of the polymorphism. However, SLC30A8 expression was positively correlated with Insulin (r=0.75, P=6.43 x 10(-6)) and Glucagon (r: 0.70, P=4.89 x 10(-5)) levels. CONCLUSIONS: The SLC30A8 rs13266634 polymorphism is among the most confirmed genetic markers of T2D in Europeans and East Asians. In isolated human islets, the risk C-allele does not affect ex-vivo insulin secretion and SLC30A8 expression, which is correlated with that of insulin and glucagon.